2005
DOI: 10.1007/bf03178859
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry parameters of BARC OcuProsta I-125 seed source

Abstract: A new model of 125I seed source, named OcuProsta seed, was designed and fabricated by Radiopharmaceuticals Division of Bhabha Atomic Research Centre for ophthalmic and interstitial applications. AAPM TG 43 recommended dosimetry parameters for this seed source were determined experimentally using TLD as well as by Monte Carlo (MC) simulation. Measured and MC calculated values of the dose rate constant (DRC) are 0.95 +/- 0.065 cGyh(-1)U(-1) and 0.972 +/- 0.005 cGyh(-1)U(-1), respectively. The mean of measured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Significant differences in g L (r) values between the Symmetra source and the other sources are observed, which are attributed to significant differences in the source design of the Symmetra seed (the active source core is consists of ceramic). The values of g L (r) of each seed model were compared with the published work [9][10][11][12][13]. A good agreement (within 2%) in g L (r) values between our study and the published work is observed for the Oncura and Symmetra seed sources [10,11].…”
Section: Radial Dose Functionsupporting
confidence: 58%
See 3 more Smart Citations
“…Significant differences in g L (r) values between the Symmetra source and the other sources are observed, which are attributed to significant differences in the source design of the Symmetra seed (the active source core is consists of ceramic). The values of g L (r) of each seed model were compared with the published work [9][10][11][12][13]. A good agreement (within 2%) in g L (r) values between our study and the published work is observed for the Oncura and Symmetra seed sources [10,11].…”
Section: Radial Dose Functionsupporting
confidence: 58%
“…This is due to the fact that the dosimetry studies for these sources are based on an updated photon cross-section dataset. However, a similar comparison for the OcuProsta and EchoSeed source models showed significant differences because the dosimetry studies of these sources [12,13] are based on an old photon cross-section dataset. For the SelectSeed, the agreement is reasonably good (within 2%) for most distances, with a maximum deviation of 3.6% at r = 1 mm.…”
Section: Radial Dose Functionmentioning
confidence: 89%
See 2 more Smart Citations
“…[9] We describe our initial experience and learning curve using ‘BARC 125 I Ocu-Prosta seed’ for the treatment of intraocular tumors.…”
mentioning
confidence: 99%